Revisiting tradition in Ahmad Fuadi’s Anak Rantau (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2023)
Paradoxical as it may be, Anak Rantau both problematizes the practice of outmigration tradition in Minangkabau culture, yet campaigns for the perpetuation of Minangkabau tradition at the same time. By highlighting the darker side of the impact of outmigration, the novel advises returning to the religion-based tradition which works through the revitalization of the surau, as a learning center, and less-materially oriented outmigration for remedy. Although it is apparent that the meaning of outmigration is being rearticulated in the novel, it is also inevitable to notice that the novel perceives the ecological destruction, the waning tradition, and the spiritually corrupt village as a failure of modernity, creating a learning loss among the Minangkabau’s youngsters. This paper uses Bhabha’s perspective of modernity and his theory of the Third Space of enunciation to reveal how the meaning of outmigration has been rearticulated in the novel and how it intersects with the powerful discourse of modernity. This paper tries to show that, first of all, in the attempts to rearticulate the long institutionalized outmigration tradition of Minangkabau people by questioning the virtue of its materialistic orientation, and problematizing the concept of ‘home’ and ‘rantau’, the novel actually tries to closely adhere to the Minangkabau tradition. Secondly, it also tries to show that the problem of learning loss is pronounced well in the anxieties over the undermining of Minangkabau traditional values.